Pengaruh Harga dan Promosi Terhadap Volume Penjualan Pada Kedai Dim sum di Banda Aceh - Rizka Rizka; A. Hamid; Ratna Mutia; Mahya (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2023)
The scope of this study aims to determine whether there is an effect of price and promotion on sales volume at Kedai Dim in Banda Aceh. This type of research is quantitative research that is associative. Data analysis used by researchers in this study is multiple linear regression analysis. Based on the results of the research and discussion, the tcount value for X1 (2.115) > ttable (1.782) and a significance level of 0.056 > 0.05 and the tcount value for X2 (1.985) > ttable (1.782) and a significance level of 0.070 > 0.05, it can be concluded that partially the price variable (X1) and the promotion variable (X2) have a significant effect on sales volume (Y), at Dim sum shops in Banda Aceh. While the simultaneous effect is the result of Fcount for the independent variables (price and promotion) of 6.075 with a significant level of 0.015. while the Ftable value at α = 0.05 is 3.89, the price variable and promotion variable simultaneously have a positive and significant effect on sales volume (Y) at Dim sum shops in Banda Aceh. Furthermore, the results of the coefficient of determination show that R2 50.3% independent variable (price and promotion) explains the dependent variable (sales volume) and 49.7% is influenced by other variables. Suggestions that can be given by researchers based on research findings are that it is better for Dim sum shops in Banda Aceh to apply affordable prices and promotions that are in accordance with the wishes of every consumer, where this can increase sales volume and improve business management.